2020
DOI: 10.15270/56-4-881
|View full text |Cite
|
Sign up to set email alerts
|

The Current Landscape of Child Protection Services in South Africa: A Systematic Review

Abstract: Child protection services are seen as the largest field of social work service delivery in South Africa. Repeated warnings of the 'crisis state' of child protection services have gone unheeded. The aim of this article is to determine the current landscape of child protection service delivery and research within the South African context. The developmental social welfare approach was used as the epistemological framework for this systematic review. Findings indicated a significant emphasis on statutory services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In a systematic review done by Strydom, Schiller and Orme (2020) of the current landscape of child protection services in South Africa, they indicated that research in the field of child protection places a strong emphasis on statutory services relying heavily on a child protection typology by using legislation and policy to protect children. This review also outlines the human capital and organisational constraints in rendering child protection services.…”
Section: Contextualising Children In Alternative Care In South Africamentioning
confidence: 99%
“…In a systematic review done by Strydom, Schiller and Orme (2020) of the current landscape of child protection services in South Africa, they indicated that research in the field of child protection places a strong emphasis on statutory services relying heavily on a child protection typology by using legislation and policy to protect children. This review also outlines the human capital and organisational constraints in rendering child protection services.…”
Section: Contextualising Children In Alternative Care In South Africamentioning
confidence: 99%
“…In South Africa, child and youth care fall within the broad umbrella of child welfare, though intersect with child protection, running residential institutions (homes) and aftercare centres for children placed there under the Children's Act 38 of 2005. The developmental child welfare approach calls for integrated service delivery focused on prevention, early intervention, statutory child protection, and re‐integration and aftercare services (Strydom et al, 2020). However, the service‐delivery system leaned heavily towards child protection with a strong focus ‘on legislation and statutory pressure to shield children from maltreatment’ (Strydom et al, 2020, p. 384).…”
Section: Progress In Child and Youth Carementioning
confidence: 99%
“…The developmental child welfare approach calls for integrated service delivery focused on prevention, early intervention, statutory child protection, and re‐integration and aftercare services (Strydom et al, 2020). However, the service‐delivery system leaned heavily towards child protection with a strong focus ‘on legislation and statutory pressure to shield children from maltreatment’ (Strydom et al, 2020, p. 384). Within this complex system, delineating who does what, or who should be doing what, has proved a thorny task.…”
Section: Progress In Child and Youth Carementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, children are also like adults who need others to be able to help develop their abilities because children are born with all their weaknesses so that without others the child cannot possibly reach a normal level of humanity (Bijlsma et al, 2021;Forslund et al, 2022;White et al, 2019). In essence, children cannot protect themselves from various kinds that cause mental, physical, social losses in various areas of life and livelihood (Middel et al, 2021;Strydom et al, 2020;Wessells, 2015). The child must be assisted by others in protecting himself, given his situation and condition, especially in the implementation of the Juvenile Criminal Justice that is unfamiliar to him.…”
Section: Introductionmentioning
confidence: 99%